Development of a Valid and Reliable Multidirectional Dribbling Assessment Instrument for Futsal Players - Septian Rahmawanto; Dea Ananda; Della Chantika (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2026)
Purpose of the Study: This study aimed to develop, validate, and determine the reliability of an enhanced futsal dribbling skills assessment instrument for male university students using a practical and standardized testing design suitable for indoor futsal environments. Methodology: This study used the Borg and Gall Research and Development model. Data were collected through observation sheets, Likert-scale questionnaires, digital stopwatches, expert validation forms, and dribbling performance tests. Participants included 50 and 100 male university students in small- and large-group trials. Pearson product moment correlation analysis was used to test validity and reliability. Main Findings: The instrument achieved an expert validation score of 81.43%. Large-group testing produced validity coefficients of 0.774 and 0.714, while reliability coefficients reached 0.809 and 0.813. Participant acceptance reached 90.08%. The final instrument utilized a 10 × 6 meter course integrating circular, winding, zig-zag, and straight dribbling patterns for multidirectional skill assessment. Novelty/Originality of this Study: This study developed a futsal-specific dribbling assessment instrument combining four movement patterns within a compact testing area. The instrument also provides normative performance categories for university athletes. This development advances existing futsal assessment tools by improving practicality, multidirectional technical evaluation, and objective interpretation of dribbling performance outcomes.